2015
DOI: 10.1007/s10584-015-1438-7
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between temperature and assault in New Zealand

Abstract: A number of previous studies have reported a positive relationship between ambient temperature and the incidence of violent crimes such as assault. This has led some authors to suggest that anthropogenic climate change may result in an increase in violent crime rates. In this study, we report an investigation of the relationship between temperature and assault incidence in New Zealand. Both police data listing recorded assaults as well as data from the Ministry of Health listing hospitalisations due to assault… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Investigations at the scale of individual cities, such as Dallas, TX (Gamble & Hess, ); St. Louis, MO (Mares, ; Mares, ); Philadelphia, PA (Schinasi & Hamra, ); and Tangshan, China (Hu et al, ), have uniformly demonstrated a positive relationship between temperature and violent crime. Still, other studies have produced similar findings at a broader scale, either by examining a conglomeration of data at the city or county level in the United States (Hipp et al, ; Jacob et al, ; Ranson, ), New Zealand (Horrocks & Menclova, ; Williams et al, ), or South Africa (Bruederle et al, ), or by examining annual, nationally aggregated data for the United States (Anderson et al, ; Rotton & Cohn, ), Finland (Tiihonen et al, ), Malaysia (Habibullah, ), England and Wales (Field, ), or multiple countries around the globe (Mares & Moffett, ). A recent meta‐analysis by Hsiang et al () concurred with these findings; variation in relationship strength between different crime types is a common conclusion (e.g., Rotton & Cohn, ), though aggravated and simple assault consistently yield the strongest relationship with temperature.…”
Section: Introductionmentioning
confidence: 86%
“…Investigations at the scale of individual cities, such as Dallas, TX (Gamble & Hess, ); St. Louis, MO (Mares, ; Mares, ); Philadelphia, PA (Schinasi & Hamra, ); and Tangshan, China (Hu et al, ), have uniformly demonstrated a positive relationship between temperature and violent crime. Still, other studies have produced similar findings at a broader scale, either by examining a conglomeration of data at the city or county level in the United States (Hipp et al, ; Jacob et al, ; Ranson, ), New Zealand (Horrocks & Menclova, ; Williams et al, ), or South Africa (Bruederle et al, ), or by examining annual, nationally aggregated data for the United States (Anderson et al, ; Rotton & Cohn, ), Finland (Tiihonen et al, ), Malaysia (Habibullah, ), England and Wales (Field, ), or multiple countries around the globe (Mares & Moffett, ). A recent meta‐analysis by Hsiang et al () concurred with these findings; variation in relationship strength between different crime types is a common conclusion (e.g., Rotton & Cohn, ), though aggravated and simple assault consistently yield the strongest relationship with temperature.…”
Section: Introductionmentioning
confidence: 86%
“…Mares ( 2013 ) found a relationship between temperature anomaly and crime overall, but none for homicide. Williams, Hill, and Spicer ( 2015 ) found a positive relationship between temperature anomaly and assaults. Schinasi and Hamra ( 2017 ) found that violent crime was strongly associated with temperature deviations.…”
Section: Our Studymentioning
confidence: 99%
“…Not surprisingly, with rapidly accumulating evidence of a global climate change, more and more studies focus on the effects of climate change on the rates of violent offending (Anderson and Delisi, 2011; Anderson et al, 1997; Hsiang et al, 2013; Mares, 2013a, 2013b; Mares and Moffett, 2016, 2019; Ranson, 2014; Rotton and Cohn, 2003; Williams et al, 2015). Previous US national-level studies have relied on Uniform Crime Report (UCR) data during their examination of the relationship between climate change and crime (see Ranson, 2014; Rotton and Cohn, 2003; Harp and Karnauskas, 2018; Mares and Moffett, 2019).…”
Section: Introductionmentioning
confidence: 99%